2011
DOI: 10.5897/ajpp11.239
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic and antioxidant activities of avocado fruit pulp on high cholesterol fed diet in rats

Abstract: Avocado, Persea americana Mill. (Lauraceae) is a widely consumed fruit in many countries for its nutritional and medicinal benefits. In the present study, avocado fruit pulp (AFP) was investigated for its anti-hyperlipidemic and antioxidant activities in Wistar albino rats. Hyperlipidemia in the animal was induced by feeding high cholesterol diet (HCD) for 70 days in standard chow diet. Rats on HCD showed significant increase in serum liver marker enzymes (GOT, GPT, GGT, ALP) and bilirubin levels; cholesterol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The activity of the extract is dose dependant and is comparable to the standard drug at the highest concentration (500 mg/kg). A similar observation had been previously reported after oral administration of avocado fruit pulp to hyperlipidemic rats [25]. The ability of the plant extract to protect against reduction in albumin or total protein resulting from a high cholesterol diet may be attributed to its free radical scavenging properties [17].…”
Section: Resultssupporting
confidence: 65%
“…The activity of the extract is dose dependant and is comparable to the standard drug at the highest concentration (500 mg/kg). A similar observation had been previously reported after oral administration of avocado fruit pulp to hyperlipidemic rats [25]. The ability of the plant extract to protect against reduction in albumin or total protein resulting from a high cholesterol diet may be attributed to its free radical scavenging properties [17].…”
Section: Resultssupporting
confidence: 65%
“…Some food components could act as antioxidants to suppress the lipid oxidation. Al-Dosari (2011) reported that avocado fruit pulp exhibited great antioxidant property in high-cholesterol-fed rats, representing as significantly reducing the MDA concentration. Chen, Liu, Zhu, Xu, and Li (2011) found that soybean oligosaccharides were able to enhance SOD activity by reducing oxidative stress in the liver of HF-fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a significant increase in non‐protein sulfhydryl and TP contents in both tissues. These results suggested that avocado showed hypocholesterolemic and antioxidant properties because of its phytoconstituents contents (Al‐Dosari, ). Avocado seed flour (125, 250, and 500 mg/kg/day, by gavage, for 2 weeks) was administered to HCD mice.…”
Section: Effect On Lipid Profilementioning
confidence: 95%